Identification and description of distinct B chromosomes in Cyphocharax modestus (Characiformes, Curimatidae) - Santos, Lessandra Viviane de Rosa [UNESP]; Foresti, Fausto [UNESP]; Martins, Cesar [UNESP]; Oliveira, Claudio [UNESP]; Wasko, Adriane Pinto [UNESP] (Sociedade Brasileira de Genética, 2008)
Cytogenetic analyses were performed in Cyphocharax modestus, collected at Paranapanema River and Tietê River (São Paulo State, Brazil). A karyotype with 2n = 54 chromosomes was observed in the animals from both Brazilian freshwater river systems. One to four B chromosomes were also detected in individuals from the Paranapanema River, which represents the probable first report of more than a single supernumerary element in a species of the Curimatidae group. C-banding revealed centromeric and telomeric heterochromatin blocks in several chromosomes of the normal karyotype complement of C. modestus. Moreover, while some B chromosomes were characterized by the complete absence of C-bands, others were totally heterochromatic. Although there was a prevalence of B chromosomes in males of C. modestus, at least one supernumerary element was found in males and/or females of several other populations of the species, which suggests that the presence of these chromosomes seems to represent a general trait of C. modestus. A possible origin of the described B chromosomes may be related to the occurrence of a chromosome non-disjunction followed by the loss of euchromatic segments, an event that should have occurred in chromosomes that present conspicuous centromeric heterochromatic blocks and even in chromosomes that lack C-bands in this region, resulting in small supernumerary elements.
Keywords: B chromosomes; C-banding; Curimatidae; Cyphocharax modestus; supernumerary chromosomes